Motivações e ações para ocultação e acumulação do conhecimento na perspectiva de líderes e liderados, em empresas do setor de serviços, no Brasil - Jardim, Letícia Pereira (2022)
The knowledge sharing should be encouraged in companies, because if it does not occur, it can generate unproductivity, business, financial and psychological losses. When knowledge is not shared, it is hidden and accumulated. Knowledge hiding is defined as intentionally not sharing knowledge that others have requested while the accumulation of knowledge is the intentional non-sharing of knowledge not requested by others, but if shared, can be useful. The motivations for hiding or accumulating knowledge are determining factors for behavior and originate from the will of individuals to have good results in organizations. The objective of this study is to analyze and compare the motivations for hiding and accumulating knowledge and the actions to discourage them, from the perspective of leaders and followers, in companies of the service sector in Brazil. For this, a qualitative study was developed, where twenty-two semi-structured interviews were conducted in companies of the service sector in Brazil. Nine motivations for hiding and accumulating knowledge were found, being two motivations that influence both hiding and accumulating knowledge. And eleven actions were found to discourage hiding or accumulating knowledge. The results show that the suggested actions to discourage the hiding and accumulation of knowledge are consistent with the motivations found and, as they are implemented in organizations, tend to reduce the non-sharing of knowledge.